Multifactor Evaluation of Good Manufacturing Practices Implementation on Cuttlefish Products in Cold Storage PPN Brondong, Lamongan - Farinsyah, Hikmah; Wahyu Santoso; Gyska Indah Harya (Grouper, 2025)
This study aims to evaluate the main components of Good Manufacturing Practices (GMP) in the processing of cuttlefish products at the Cold Storage facility of PPN Brondong, Lamongan. GMP plays a crucial role in ensuring the quality and safety of fishery products to meet export standards. Data analysis was conducted using a factor analysis approach with the assistance of SPSS version 25. The results of the KMO test (0.777) and Bartlett’s test indicate that the data is suitable for analysis. Eight GMP variables were successfully grouped into five main factors, which together explain more than 90% of the data variation. The most influential factors identified were packaging and labeling, storage, sanitation facilities, transportation, and the selection of raw and auxiliary materials. The strength of this research lies in its comprehensive approach to evaluating eight key GMP variables through factor analysis, an approach that has rarely been applied in similar studies. These findings provide a critical foundation for strengthening GMP implementation to enhance the quality and competitiveness of Indonesian cuttlefish products in the global market.